Implementing quality management strategies improves clinical quality as a voluntary medical male circumcision program in Namibia matures: a process analysis - Gillian O'Bryan; Alison Ensminger; Idel Billah; Edwin Sithole; Magdaleena Nghatanga; Laura Brandt; Mark Shepard; Mekondjo Aupokolo; Assegid Tassew Mengistu; Norbert Forster; Brigitte Zemburuka; Gram Mutandi; et al. (BMC, 2023)
Abstract Background Surgical voluntary medical male circumcision (VMMC) is a safe procedure; however, maintaining quality standards at scale, particularly during scale-up, is a challenge making ongoing quality management (QM) efforts essential. This study describes program quality measured by rates of adverse events (AEs) over four years of VMMC implementation in Namibia, compares AE rates over time, and discusses QM processes that contextualize AE trends and illustrate improvements in quality as the program matured. The International Training and Education Center for Health (I-TECH) assisted the Namibian Ministry of Health and Social Services (MoHSS) in expanding VMMC in three regions among boys and men over 10 years of age between January 2015 and September 2019. Methods A comprehensive package of QM strategies was implemented by multi-disciplinary onsite teams with support from national and international technical advisors. Retrospective routine MoHSS data from the VMMC register, client forms, and monthly AE reports were collected during implementation in the three regions to assess the impact of QM interventions on AEs and to calculate the proportion of clients who experienced AEs over time. The proportion of clients who experienced an AE over time was compared using a Cochran-Armitage test for trend. Results Between January 2015 and September 2019, 40,336 clients underwent VMMC and 593 (1.5%) clients experienced a post-operative AE in the three supported regions. The AE rate was highest in the first quarter of clinical service delivery in each region (January-March 2015 in Oshana and Zambezi, October-December 2017 in //Kharas) but declined over the implementation period as the program matured. This observed trend between program maturity and declining AE rates over time was significant (p < 0.001) when compared using a Cochran-Armitage test for trend. Conclusions As the I-TECH-supported VMMC program matured, QM measures were introduced and routinized, and clinical quality improved over time with the rate of AEs decreasing significantly over the implementation period. Applying systematic and continuous QM processes and approaches across the continuum of VMMC services and considering local context can contribute to increased clinical safety. QM measures that are established in more mature program sites can be quickly adopted to respond to quality issues in program expansion sites.